Dinâmica de anticorpos em cães submetidos a diferentes protocolos de tratamento para leishmaniose visceral canina - Costa, Eliesse Pereira (2024)
Visceral leishmaniasis is a zoonotic disease that has a significant impact on public health. Dogs are the main urban reservoirs of Leishmania spp. infection. In this study, we evaluated the dynamics of antibodies in dogs that were treated with different therapeutic protocols for canine visceral leishmaniasis (CVL). Therefore, serum antiLeishmania spp. antibody (IgG) titers were considered and clinical scores were performed according to Brasileish (2018) guidelines, in order to verify the correlations of these variables. This research included 23 dogs naturally infected by Leishmania spp. which were grouped based on the treatment protocol defined by clinical veterinarians: G1 were treated with allopurinol (n = 6); G2 were treated with allopurinol in combination with Milteforan® (n = 10); and G3 were treated with allopurinol associated with Milteforan® and the LeishTec® vaccine (n = 7). The dogs were monitored monthly for a period of one year. To verify serum antibody titers, an indirect immunofluorescence reaction was performed. We found that dogs from G1 and G2 had lower clinical scores and antibody titers, when compared to the parameters evaluated in pre-treatment; however, clinical relapses were observed in three animals. In G3, clinical scores were lower than pre-treatment; however, they presented relatively stable antibody titers and no clinical relapse was observed. It should be noted that, due to the challenges of parasitic loads in infections, the immune response of animals must be considered in controlling the infection. Furthermore, it is highlighted that the evaluation of antibodies in isolation does not constitute a good parameter for therapeutic evaluation. Therefore, it is necessary to include other criteria that make it possible to determine the parasite load, verify the most appropriate therapeutic protocol for CVL and establish the reservoir status of infected and treated dogs.